European molecular epidemiology and strain diversity of feline calicivirus. (30th January 2016) - Hou, J.; Sánchez‐Vizcaíno, F.; McGahie, D.; Lesbros, C.; Almeras, T.; Howarth, D.; O'Hara, V.; Dawson, S.; Radford, A. D.
Abstract : Feline calicivirus (FCV) causes a variable syndrome of upper respiratory tract disease, mouth ulcers and lameness. A convenience‐based prospective sample of oropharyngeal swabs (n=426) was obtained from five countries (France, Germany, Greece, Portugal and the UK). The prevalence of FCV by virus isolation was 22.2 per cent. Multivariable analysis found that animals presenting with lymphoplasmacytic gingivitis stomatitis complex were more likely to test positive for FCV infection. Furthermore, vaccinated cats up to 48 months of age were significantly less likely to be infected with FCV than unvaccinated animals of similar ages. Phylogenetic analysis based on consensus sequences for the immunodominant region of the capsid gene from 72 FCV isolates identified 46 strains. Thirteen of the 14 strains with more than one sequence were restricted to individual regions or sites in individual countries; the exception was a strain present in two sites close to each other in France. Four strains were present in more than one household. Five colonies, four of which were rescue shelters, had multiple strains within them. Polymerase sequence suggested possible rare recombination events. These locally, nationally and internationally diverse FCV populations maintain a continuous challenge to the control of FCV infection and disease.